4th Annual Progress Reporting and Coordination Meeting on CCAFS Projects and Climate-Smart Village Implementation in Southeast Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The proceedings document the results of the 4th Annual Progress Reporting and Coordination Meeting on CCAFS Projects and Climate-Smart Village Implementation in Southeast Asia. The report tackles the progress of activities in the CSV sites and on CCAFS project implementation in 2018; the significant outputs and outcomes of FP/CSV implementation; and the knowledge, learning, and experiences across CSVs and projects.